Stable dispersions of azide functionalized ferromagnetic metal nanoparticles. Issue 10 (18th December 2014) - Hofer, C. J.; Zlateski, V.; Stoessel, P. R.; Paunescu, D.; Schneider, E. M.; Grass, R. N.; Zeltner, M.; Stark, W. J.
Abstract : Stable dispersions of azide functionalized ferromagnetic metal nanoparticles were synthesized by covalent attachment of a block-copolymer to the nanoparticles surface via SI-ATRP and subsequent post-modification. Abstract : Ferromagnetic nanoparticles are covalently modified in order to enhance the dispersion stability as well as the antifouling properties. Insertion of an azide moiety allows "click"-reaction of a relevant tag molecule. This and the high saturation magnetization of the presented nanocomposite offer a promising platform for magnetic biosensors.